Mining, resistance, and repression in Honduras: between law and lawlessness - Middeldorp, Nick (2016)
The expansion of the mining frontier in Honduras provokes resistance of an anti-mining movement, which mobilizes rural communities to declare their municipalities free of mining. Meanwhile, the mining industry can circumvent the legal right to consultation by the criminalization of protest and the use of violence. This article plants serious concerns about this tendency, but also shows how social movements can adapt and develop successful resistance in complex political and juridical environments.